Effect of artificial aging on physicochemical properties of bone char and adsorption properties of Cd2+ - Linchao Hu; Jinbao Wan; Kaixin Tang; Haoran Yu; Tao Huang; Dongyuan Fan; Wenyi Zhang; Linqiang Mao (Carbon Trends)
Biochar is a good adsorbent and has been widely used to repair heavy metal soils. However, aging will affect the physical and chemical properties of biochar, and then affect its adsorption performance on heavy metals. This study explored the impact of aging on the adsorption performance of biochar derived from bovine bone char, prepared at 350 °C and 550 °C through oxygen-limited carbonization. The bone chars were simulated aging by H2O2 and Na2S2O8, with Cd2+ as the target ions for adsorption. This study examined the effect on the physical and chemical properties of bone char prepared by different aging degrees, assessing its adsorption efficiency for Cd. The results showed that the oxidative aging led to a rough surface and increased Cd adsorption. The surface of bone char was smooth and bar like without obvious granular matter after acidification aging, inhibiting Cd adsorption. In addition, Oxidation aging increased the surface complexation of bone char and decreased ion exchange. The coprecipitation of bone char and the cationic Caution-π action were seriously inhibited by acidification aging. The findings of this study provide valuable insights and promising applications for the use of animal bones as a strategy for the remediation of Cd2+ pollution.